EFFECT OF COMPETITION ON INNOVATIVE DEVELOPMENT AND COMPETITIVENESS OF ECONOMY - V. Lagutin; U. Yasko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
There was investigated the interaction of competition, innovation development and competitiveness of the economy. Authors insist that creation of conditions for conscientious competition is one of the most important stimulus for innovative development. The model of effective competition is described and is showed the significant role of rapid introduction of innovations. Financial activity and the dynamic of innovation introduction of industrial companies is analyse. The position of Ukraine in innovation sphere is showed in global ranking. The positive tendency of software market growth is described through extending of their specialization and outsourcing on the world market. Authors state that economic competition is the base for innovative development.